ANALISIS PERBANDINGAN TINGKAT KESEHATAN BANK DIGITAL DAN BANK KONVENSIONAL BERTRANSFORMASI DIGITAL DI INDONESIA: PENDEKATAN RGEC PERIODE 2021–2025 - Behuku, Jitro G.; Pangemanan, Kevin; Makinggung, Juliet P. T.; Tiwatu, Irvans R. C. (MANAJEMEN ADMINISTRASI BISNIS DAN PEMASARAN, 2026)
This study examines the comparative financial soundness of digital banks and conventionallytransforming banks in Indonesia using the RGEC (Risk Profile, Good Corporate Governance, Earnings, Capital) framework over the period 2021–2025. Employing a quantitative-comparative design with purposive sampling, the study analyzes 50 observations from 10 banks—five digital banks(ARTO, AGRO, BBHI, BBYB, AMAR) and five conventionally-transforming banks (BMRI, BBRI, BBTN, BNGA, NISP). After conducting Shapiro-Wilk normality tests confirming non-normal distributions across most variables, Mann-Whitney U tests were applied. Results indicate nostatistically significant differences in NPL (p = 0.655), LDR (p = 0.073), and ROA (p = 0.079).Significant differences were found in GCG (p < 0.001; r = 0.517), NIM (p < 0.001; r = 0.594), and CAR (p < 0.001; r = 0.808). Digital banks demonstrate superior NIM and CAR but substantially weaker GCG and ROA, reflecting the institutional immaturity and high investment phase characteristic of nascent digital banking models. Conventionally-transforming banks show stronger governance, profitability, and intermediation balance. These findings underscore a fundamental trade-off between digital agility and institutional maturity in Indonesian banking